App-based supplemental exercise in rehabilitation, adherence, and effect on outcomes: a randomized controlled trial. (August 2020) - Li, Ingrid; Bui, Tram; Phan, Hoang T; Llado, Ana; King, Clayton; Scrivener, Katharine
Question: To determine the uptake of an app-based supplemental exercise programme in a rehabilitation setting and the effect of such a programme on length of stay and function compared to usual care physiotherapy. Design: Randomized controlled trial with random allocation and assessor blinding. Participants: A total of 144 individuals with mixed diagnoses (orthopaedic, neurological, reconditioning) admitted for inpatient sub-acute rehabilitation. Interventions: Participants were randomly allocated to usual care physiotherapy (control group) or usual care physiotherapy with the addition of an app-based supplemental exercise programme (intervention group). Outcome measures: The primary measure of interest was total supplementary exercise dosage completed by the intervention group. The primary between-group outcome measure was length of stay with secondary measures including walking endurance (Six-Minute Walk Test), walking speed (10-Metre Walk Test), functional mobility (Timed Up and Go Test) and level of disability (Functional Independence Measure). Results: Participants in the intervention group performed 7 minutes (SD: 9) or 49 repetitions (SD: 48) of supplementary exercise using the app each day. There were no differences between the groups for length of stay (mean difference (MD): −0.5 days, 95% confidence interval (CI): −3.2 to 2.2) or change in any secondary functional outcome measures, including walking speed (MD: −0.1 m/s, 95% CI: −0.2 to 0.0) and disability (MD: −0.9, 95% CI: −3.6 to 1.8). Conclusion: A small supplementary exercise dose was achieved by participants in the intervention group. However, such a programme did not affect length of stay or functional outcomes when compared to usual care.